Diseño de un sistema de indicadores de gestión para el proceso de producción de una empresa avícola, ubicada en la ciudad de Guayaquil - Lainez Rosales, Shirley Giomar (2010)
This work consists of implementing a system management indicators for the production process of a company dedicated to the hatching of eggs, chicken rearing up, located in the city of Guayaquil. The implementation was done through three basic steps. The main purpose of the indicators is to help measure and improve future situations. The first chapter is the framework theoretically explained in detail everything about the system management indicators, key implementation concepts computer. The knowledge of the business of the company in which implemented the management system of indicators is presented in the second chapter. The third chapter focuses on the development of the system management indicators, detailing the production process to evaluate and design of the indicators to be implemented. In the fourth chapter describes the functionality of software designed for management indicators. The fifth chapter provides an analysis system of management indicators in place and making decisions. The conclusions and recommendations of this study are presented in chapter six.